2017
DOI: 10.1159/000452841
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Cortical Spreading Depolarization and Seizures

Abstract: Cortical spreading depolarization (CSD) is an electrophysiologic phenomenon found mostly in the setting of neurologic injury resulting in the disturbance of ion homeostasis and leading to changes in the local vascular response. The bioelectric etiology of CSD shares similarities to those in epileptic disorders, yet the relationship between seizures and CSD is unclear, with several studies observing cortical depression before, during, and after seizure activity, thus obscuring our understanding of whether CSD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,570 publications
(41 citation statements)
references
References 95 publications
1
36
1
1
Order By: Relevance
“…Conversely, stimulation-induced recurrent epileptiform discharges have been shown to block cortical and subcortical SD in rats ( 164 ). These findings do not allow a single interpretation of the interplay between SD and epilepsy, but they strongly suggest that there is a common mechanism in which a pivotal role may be played by NMDA receptors ( 165 ).…”
Section: Sd In Disease Conditionsmentioning
confidence: 90%
“…Conversely, stimulation-induced recurrent epileptiform discharges have been shown to block cortical and subcortical SD in rats ( 164 ). These findings do not allow a single interpretation of the interplay between SD and epilepsy, but they strongly suggest that there is a common mechanism in which a pivotal role may be played by NMDA receptors ( 165 ).…”
Section: Sd In Disease Conditionsmentioning
confidence: 90%
“…SD-induced spreading ischemia is so severe that it dramatically delays the energy-dependent recovery of SD and even leads to widespread necrosis of cortical neurons and astrocytes [4]. Experimental and clinical data has demonstrated that SD occurs abundantly after aneurysmal subarachnoid hemorrhage, intracerebral hemorrhage, traumatic brain injury, malignant hemispheric stroke, and epilepsy and plays an important role in secondary brain injury [5][6][7][8]. Moreover, SD is the pathophysiological substrate of migraine aura and a trigger for headache [9].…”
Section: Setup Requirements For Oismentioning
confidence: 99%
“…6 Spreading depression was first described by Leão as a slowly propagating wave of complete cortical electrogram flattening following epileptic discharge evoked by tetanic electrical stimulation during alternate current (AC) electroencephalographic (EEG) recordings. 6 Spreading depression was first described by Leão as a slowly propagating wave of complete cortical electrogram flattening following epileptic discharge evoked by tetanic electrical stimulation during alternate current (AC) electroencephalographic (EEG) recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors promoting SD (high potassium, low magnesium, enhanced synaptic activity, glutamate receptor agonists) also promote seizures and moreover, seizures and SD frequently co-occur in various experimental models and patients. 6 Spreading depression was first described by Leão as a slowly propagating wave of complete cortical electrogram flattening following epileptic discharge evoked by tetanic electrical stimulation during alternate current (AC) electroencephalographic (EEG) recordings. 7 Large negative shifts were later described during SD 8 using full-band direct current (DC)-coupled recordings, which are now considered the gold standard for SD detection.…”
Section: Introductionmentioning
confidence: 99%